ByzRev 07.2025.074: Ahmet Arı, The Sion Treasure Reconsidered: The Biographies and Multivalence of Sacred Silver Objects in Sixth-Century Byzantium: (Studies in Byzantine Cultural History). Abingdon: Routledge 2024. - Pitarakis, Brigitte (The Byzantine Review, 2025)
Ahmet Arı, The Sion Treasure Reconsidered: The Biographies and Multivalence of Sacred Silver Objects in Sixth-Century Byzantium (Studies in Byzantine Cultural History). Abingdon: Routledge 2024. xv+196 pages, 63 figures, 4 tableaux, 1 diagramme. – ISBN 978-1-032-38535-8 (hbk), ISBN 978-1-032-38535-5 (pbk), 978-1-032-38535-3 (ebk)